2003
DOI: 10.1046/j.1365-2249.2003.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of proteinase 3 in patients with anti-neutrophilic cytoplasmic autoantibodies-associated systemic vasculitis in remission

Abstract: SUMMARYIn systemic small vessel vasculitides, patients form autoantibodies against neutrophil granular proteins, anti-neutrophilic cytoplasmic autoantibodies (ANCA). Some correlation is seen between ANCA titre and disease activity, but whether this is cause or effect is still unknown. It has been reported that levels of proteinase 3 (PR3), one of the main ANCA antigens, are increased in patients with active disease. An increased level of circulating antigen could mean a predisposition to autoimmunity. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 29 publications
(32 reference statements)
8
52
2
Order By: Relevance
“…Experiments performed by our group, have shown that the plasma levels of mature PR3 as well as pro-PR3 are elevated in AASV [114,115,116]. It was also observed that mPR3 + neutrophils are more abundant in AASV compared to healthy donors, which agrees with previous studies suggesting that a high percentage of mPR3 + cells may be a risk factor for vasculitis [78,115].…”
Section: Recent Updatessupporting
confidence: 81%
“…Experiments performed by our group, have shown that the plasma levels of mature PR3 as well as pro-PR3 are elevated in AASV [114,115,116]. It was also observed that mPR3 + neutrophils are more abundant in AASV compared to healthy donors, which agrees with previous studies suggesting that a high percentage of mPR3 + cells may be a risk factor for vasculitis [78,115].…”
Section: Recent Updatessupporting
confidence: 81%
“…However, these reports may not be applicable to an adult cardiac surgery population. NGAL is expressed by atherosclerotic vascular tissue (21,22), which may itself be up-regulated in the early postoperative period, and chronic renal disease is a marker for generalized atherosclerosis, potentially enhancing the contribution of extrarenal NGAL in such patients. Furthermore, although animal models indicate systemic NGAL filtered at the renal glomerulus is rapidly and efficiently reabsorbed by the proximal renal tubule (20), this may not be the case in the setting of chronic renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the histological findings of NETs in biopsies, elevated levels of NETs in the circulations have also been identified in patients (Table I) (Kessenbrock et al 2009, Surmiak et al 2015, Surmiak et al 2016). Similar results as for NETs have been obtained for NET-associated components such as HMGB1, calprotectin, PR3, MPO, and NE as well as mtDNA when measured separately in the circulation (Table 1) (Henshaw et al 1994, Haubitz et al 1997, Ohlsson et al 2003, Wibisono et al 2010, Bruchfeld et al 2011, Pepper et al 2013, Surmiak et al 2016). …”
Section: Presence In Biopsies and Plasma/serumsupporting
confidence: 66%
“…Our finding suggests a dual role for ANCA of which some also are involved in clearance of NET remnants from the circulation, possibly through opsonization. We have previously also reported on an inverse relationship between ANCA and PR3/α1-antitrypsin complexes in the circulation (Ohlsson et al 2003).…”
Section: P=0048)mentioning
confidence: 99%